Igor’s Goriest Tune and Selected Text Pieces - Barkin, Elaine R. (Current Musicology, 2013)
To observe my 50th birthday in 1982, I conceived Igor’s Goriest Tune and sent it out to friends, colleagues and family members. In 1987 IGT became part of a limited edition of graphic–texts—IMAGE: a collection (with four pieces of mine and works by Jim Randall, Bob Paredes, Jane Coppock, Ben Boretz, and Catherine Schieve; the first publication of OPEN SPACE in 1989 was IMAGE ). IGT also appeared in e: an anthology, a collection of my writings and graphics (1975–1995) published by OPEN SPACE. And so, to celebrate, to celebrate—echoes of Purcell flood in!—David Gutkin’s invitation to participate in this issue of Current Musicology, here’s Igor!